The Arabian Milieu: How Pre-Islamic Culture and Language Shaped the Form and Content of the Quran - Dr. Muhammad Zakariya (Journal of Religion and Society, 2025)
This paper investigates the deep interconnection between the pre-Islamic Arabian milieu and the Quran, arguing that the revelation's linguistic form and substantive content are inextricably linked to its historical context. It delves into the sophisticated Arabic literary culture, tribal customs, and religious beliefs of the era to trace their influence on the Quran's stylistic choices, metaphorical language, and legislative addresses. The research reveals that the Quran utilized the familiar linguistic and conceptual framework of its first audience to convey its message effectively, while simultaneously redefining key terms and concepts such as honor (ird), nobility (hasab), and sanctity (hurmah). This study concludes that a nuanced appreciation of this cultural-linguistic embeddedness is essential for a historical-philological understanding of the Quran, highlighting its nature as a text that profoundly transformed the very medium it employed. Keywords: Pre-Islamic Arabia, Quranic Language, Historical Philology, Arabian Milieu, Cultural Linguistics, Tribal Society, Revelation and Context.